Sacrifice and violence: reflections from an ethnography in Nepal - Lecomte-Tilouine, Marie (Cambridge University Press & Assessment, 2024)
Violence is at the heart of the sacrifice, despite its denial in the texts. For the participants and observers, it materialises in the exposure of everyone and everything to the 'fountains of blood'. The specificity of this public and holistic violence, orchestrated in Nepal by the highest dignitaries and aimed at the rejuvenation of the cosmic, political and social order, allows us to see sacrifice as the ultimate model of legitimate violence. At the same time, observation reveals its oxymoronic nature through the opposite effect its violence has on its participants. As such, sacrifice is not only the organiser of society, but also the revelator of its internal tensions and fault lines. The book explores the complex aspects of royal ceremonies, their contestation by different groups, and finally the contours of the new legitimacy that sacrifice found during the revolutionary period under its most extreme form of human sacrifice.